Incorporation of Uridine into Bacillus subtilis and SPP1 Bacteriophage Deoxyribonucleic Acid - Barlati, Sergio (1970)
Tritiated uridine is incorporated into the deoxyribonucleic acid of Bacillus subtilis and bacteriophage SPP1; the tritium is recovered in the cytidine moiety of both deoxyribonucleic acids.